Radiation Treatment for WHO Grade II and III Meningiomas - Walcott, Brian P.; Nahed, Brian V.; Brastianos, Priscilla K.; Loeffler, Jay S. (Frontiers in Oncology, 2013)
The treatment of meningiomas is tailored to their histological grade. While World Health Organization (WHO) grade I lesions can be treated with either surgery or external beam radiation, WHO Grade II and III lesions often require a combination of the two modalities. For these high-grade lesions, conventional external beam radiation is delivered to either the residual tumor or the surgical resection margin. The optimal timing of radiation, either immediately following surgical resection or at the time of recurrence, is yet to be determined. Additionally, another method of radiation delivery, brachytherapy, can be administered locally at the time of surgery for recurrent lesions. Altogether, the complex nature of WHO grade II and III meningiomas requires careful treatment planning and delivery by a multidisciplinary team.